The effect of market distress on mutual fund performance: international evidence - Choonara, Yasmin Marques (2019)
In this paper, we use a comprehensive sample of equity mutual funds from 34 countries around the world during the 1999-2015 period to study the impact of market distress on mutual fund performance. Our results show that in periods of market distress mutual funds perform worse in more competitive countries. This is because, in these countries, investors are more sophisticated and, therefore, react more to market downturns by heavily withdrawing their money. As a result, mutual fund managers are forced to rebalance their portfolios selling assets immediately, particularly those with higher risktaking positions, at distressed or “fire sale” prices and therefore experiencing severe losses. Coval and Stafford (2007) show that “fire sales” in mutual funds that experience large outflows lead to a negative stock price pressure. “Fire sales” are therefore expected to more greatly affect fund performance in countries with more active investors.